Influence of base of support on early postural adjustments and fencing lunge performance - Akbas, A.; Marszalek, W.; Bacik, B.; Juras, G. (Sports Biomechanics, 2021)
The aim of the study was to examine whether the width of the base of support (BOS) has an influence on early postural adjustments (EPA) and armed upper limb and COM kinematics during lunging. Eight elite female fencers participated in the study. The displacement of the centre of foot pressure (COP) and kinematics of centre of mass (COM) were recorded using force platforms. The kinematics of the wrist of the armed upper limb were obtained using a 3D accelerometer. The results show that EPA were characterised by a very small COP displacement (about 0.6 to 1.2 cm). The COP amplitude showed a tendency to decrease with an increase in BOS width under reaction time conditions. In contrast, a greater BOS width was associated with a significant increase in COM acceleration at foot-off and peak COM acceleration during lunging also under reaction time instructions. The kinematics of the wrist were not influenced by BOS. The results show that in elite fencers, the upper limb movement is dissociated from the whole body movement. We suppose that a small COP amplitude is a postural skill which is integrated into the lunging skill and might influence the acceleration of COM.